Blue moon [videorecording (DVD)] - Hadlow, Mark; Brophy, Jed; Hadlow, Olivia; Brooks, Doug (Syndicado, 2021)
Businessman Horace Jones is deep in debt. While his family thinks he is in Hong Kong on a business deal, he is covertly working a quiet nightshift in a gas service station to make ends meet. When a suspicious looking character dies in the station's toilet clutching a wad of cash, Horace is suddenly offered a tempting opportunity to dispose of the evidence and solve his own financial problems. When gangster Darren arrives at the station store, the screws begin to tighten on Horace's desperate scheme. Forty years of anger and resentment boil to the surface as the two men realize they know each other.